Influence of powder characteristics on the structural and the mechanical properties of additively manufactured Zr-based bulk metallic glass. (1st November 2021) - Wegner, Jan; Frey, Maximilian; Piechotta, Markus; Neuber, Nico; Adam, Bastian; Platt, Sebastian; Ruschel, Lucas; Schnell, Norman; Riegler, Sascha Sebastian; Jiang, Hao-Ran; Witt, Gerd; Busch, Ralf; et al.
Graphical abstract: Highlights: The flowability of ZrCuAlNb powder improves with flow aid and coarser particles. Preexisting crystals in the powder feedstock vanish during laser powder bed fusion. The O2 content within the powder impacts the applicable parameter range. ·The Laser power predominantly fosters crystallization compared to the scan speed. An O2 contamination >1600°µg/g drastically decreases the flexural strength. Abstract: Additive manufacturing of Zr-based bulk metallic glasses (BMGs) is subject to growing scientific and industrial attention. Laser-based powder bed fusion of metals (PBF-LB/M) becomes a key technology to overcome current restrictions of size and geometry in the manufacturing of BMGs. For industrial application, further knowledge about defect formation, such as porosity and crystallization, is mandatory to develop processing strategies and suitable quality assurance. In this context, the influence of the particle size distribution, oxygen contamination, and applied process parameters during the PBF-LB/M of the glass-forming alloy AMZ4 (in at.% Zr59.3 Cu28.8 Al10.4 Nb1.5 ) on the structural and mechanical properties were evaluated. It was found that the addition of SiO2 flow aid to the feedstock is suitable to increase flowability without impeding fabrication of the amorphous material. Furthermore, the processing of partially crystalline powder particles into amorphous samples is demonstrated. It indicates that today's high effort producing amorphous powders and thus the production costs can be reduced. Flexural bending tests and high-energy synchrotron X-ray diffraction reveal that the powder feedstock's oxygen content is crucial for the amorphization, embrittlement, and flexural strength of PBF-LB/M processed Zr-based BMGs.